Brain fogginess, gas and bloating: a link between SIBO, probiotics and metabolic acidosis - Rao, Satish S. C. (Clin Transl Gastroenterol, 2018)
BACKGROUND: D-lactic acidosis is characterized by brain fogginess (BF) and elevated D-lactate and occurs in short bowel syndrome. Whether it occurs in patients with an intact gut and unexplained gas and bloating is unknown. We aimed to determine if BF, gas and bloating is associated with D-lactic acidosis and small intestinal bacterial overgrowth (SIBO). METHODS: Patients with gas, bloating, BF, intact gut, and negative endoscopic and radiological tests, and those without BF were evaluated. SIBO was assessed with glucose breath test (GBT) and duodenal aspiration/culture. Metabolic assessments included urinary D-lactic acid and rblood L-lactic acid, and ammonia levels. Bowel symptoms, and gastrointestinal transit were assessed. RESULTS: Thirty patients with BF and 8 without BF were evaluated. Abdominal bloating, pain, distension and gas were the most severe symptoms and their prevalence was similar between groups. In BF group, all consumed probiotics. SIBO was more prevalent in BF than non-BF group (68 vs. 28%, p = 0.05). D-lactic acidosis was more prevalent in BF compared to non-BF group (77 vs. 25%, p = 0.006). BF was reproduced in 20/30 (66%) patients. Gastrointestinal transit was slow in 10/30 (33%) patients with BF and 2/8 (25%) without. Other metabolic tests were unremarkable. After discontinuation of probiotics and a course of antibiotics, BF resolved and gastrointestinal symptoms improved significantly (p = 0.005) in 23/30 (77%). CONCLUSIONS: We describe a syndrome of BF, gas and bloating, possibly related to probiotic use, SIBO, and D-lactic acidosis in a cohort without short bowel. Patients with BF exhibited higher prevalence of SIBO and D-lactic acidosis. Symptoms improved with antibiotics and stopping probiotics. Clinicians should recognize and treat this condition.